Ratio of Products of Fluctuating Two-Ray Variates - Badarneh, Osamah S.; da Costa, Daniel Benevides; Benjillali, Mustapha; Alouini, Mohamed-Slim (IEEE communications letters, 2019)
This letter provides a statistical analysis for the ratio of the products of fluctuating two-ray (FTR) random variables (RVs), in which exact expressions for the probability density function (PDF), cumulative distribution function (CDF), generalized moment generating function (MGF), which coincides with the n-th moment by setting s = 0, the amount of fading, and channel quality estimation index, are derived. To show the usefulness of the derived expressions, we study the performance of multihop wireless communication systems subject to multiple interferers. The outage probability is examined, based on which an asymptotic analysis is carried out. Monte Carlo simulations are presented to corroborate the proposed analysis.